Laser vibrometer using self-compensating system: a novel technique - Lim, Lennie Enk Ng (2008)
In this research work, the vibration measurement is done by a novel scanning laser vibrometer. The objective of this work is to eliminate the need for mechanical scanning by using an acousto optic deflector.